TIM-3/Gal-9 interaction affects glucose and lipid metabolism in acute myeloid leukemia cell lines - Rezaei, Mahnaz; Ghanadian, Mustafa; Ghezelbash, Behrooz; Shokouhi, Abolfazl; Bazhin, Alexandr V.; Zamyatnin, Andrey A.; Ganjalikhani-Hakemi, Mazdak (Frontiers in Immunology, 2023)
Introduction: T cell immunoglobulin and mucin domain-3 (TIM-3) is a transmembrane molecule first identified as an immunoregulator. This molecule is also be expressed on leukemic cells in acute myeloid leukemia and master cell survival and proliferation. In this study, we aimed to explore the effect of TIM-3 interaction with its ligand galectin-9 (Gal-9) on glucose and lipid metabolism in AML cell lines. Methods: HL-60 and THP-1 cell lines, representing M3 and M5 AML subtypes, were cultured in appropriate condition. The expression of TIM-3 on the cell surface was ascertained by flow cytometric assay. We used real-time PCR to examine the mRNA expression of GLUT-1, HK-2, PFKFB-3, G6PD, ACC-1, ATGL and CPT-1A, colorimetric assays to measure the concentration of glucose, lactate, GSH and the enzymatic activity of G6PD, MTT assay for determination of cellular proliferation and GC-MS to designate FFAs. Results: We observed the significant upregulated expression of GLUT-1, HK-2, PFKFB-3, ACC-1, CPT-1A and G6PD and the enzymatic activity of G6PD in a time dependent manner in the presence of Gal-9 compared to PMA and control group in both HL-60 and THP-1 cell lines (p>0.05). Also, the elevation of glucose consumption, lactate release and extracellular free fatty acids, the concentration of cellular glutathione (GSH) and cell proliferation was significantly higher in the presence of Gal-9 compared to PMA and control groups in both cell lines (p>0.05). Conclusion: TIM-3/Gal-9 ligation on AML cell lines results in aerobic glycolysis and altered lipid metabolism, also protects cell from oxidative stress, all in favor of leukemic cell survival and proliferation.